2023
DOI: 10.1002/adma.202208954
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Out‐of‐Plane Spin–Orbit Torque by Interfacial Modification

Abstract: SOT deterministic switching of perpendicular magnetization requires an external in-plane magnetic field to break the mirror symmetry in the current-magnetization plane. This extra magnetic field is not favored for the scalability and integration of the devices. Various efforts have been made to break the mirror symmetry by extra design of the device structures, such as a wedge shape of ferromagnetic layer, [4] titled anisotropy, [5,6] additional magnetic layer with in-plane shape anisotropy, [7,8] exchange bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Additionally, by using a two-step fabrication process, we identified that the oblique angle deposition of the bottom Pt layer, while compared to other layers, plays a more decisive role in realizing field-free currentinduced switching (see Supporting Information S5). Such two-step fabricated samples might also experience some level of interfacial oxidation, which can potentially enhance the overall DL-SOT efficiency 37,38 .…”
Section: Demonstration Of Robust Field-free Switching In Obliquely De...mentioning
confidence: 99%
“…Additionally, by using a two-step fabrication process, we identified that the oblique angle deposition of the bottom Pt layer, while compared to other layers, plays a more decisive role in realizing field-free currentinduced switching (see Supporting Information S5). Such two-step fabricated samples might also experience some level of interfacial oxidation, which can potentially enhance the overall DL-SOT efficiency 37,38 .…”
Section: Demonstration Of Robust Field-free Switching In Obliquely De...mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The SOT-driven perpendicular magnetization switching is usually studied in nonmagnetic/ferromagnetic (NM/FM) bilayers. [8,9] For the purpose of making SOT switching a feasible technology, the SOT-based devices are required to show high thermal stability and low switching current density (J c ) simultaneously. [10,11] However, the conventional SOT generated from the NM layer, is an interface effect in nature due to the exponential attenuation of spin current and short spin coherence length, that is, J c is proportional with FM thickness t FM .…”
Section: Introductionmentioning
confidence: 99%
“…The SOT consists of two mutually orthogonal vector components: damping-like torque (DLT, τ DLT ¼ m  ð m  ŝÞ) and field-like torque (FLT, τ FLT ¼ m  ŝ), where m and ŝ are unit vectors of magnetization and spin polarization. [9][10][11][12][13][14][15][16][17][18] This study explores the potential of SOT devices with perpendicular magnetic anisotropy (PMA) as a foundation for true random number generators (TRNGs) based on stochastic physics. The DLT aligns the magnetization along the y-direction.…”
Section: Introductionmentioning
confidence: 99%
“…The SOT consists of two mutually orthogonal vector components: damping‐like torque (DLT, bold-italicτDLT=bold-italicmfalse^×false(bold-italicmfalse^×bold-italicsfalse^false)) and field‐like torque (FLT, bold-italicτFLT=bold-italicmfalse^×bold-italicsfalse^), where truem^ and trues^ are unit vectors of magnetization and spin polarization. [ 9–18 ]…”
Section: Introductionmentioning
confidence: 99%